PENGUJIAN INDIKATOR EKOLOGIS PERIKANAN BERKELANJUTAN: STRUKTUR KOMUNITAS HASIL TANGKAPAN IKAN DI KABUPATEN KOTABARU, KALIMANTAN SELATAN - Am Azbas Taurusman (Institut Pertanian Bogor, 2011)
To achieve sustainable fisheries management needs appropriate and validated indicators. The purpose of this study is to evaluate the ecological indicator of sustainable fisheries base on fishery statistic data. The analyses of diversity, similarity, and clusters were conducted on landing data of fisheries statistic for ten years of 1995-2005 in Kotabaru District. Result of this study indicated the variations of diversity parameters of catch in this area. Characteristic taxa of the catch in Kotabaru were family Penaeidae (shrimp), Scombridae (mackerel), Clupeidae, and Carangidae. The group of demersal fish was mostly exploited during the year 1995-2005 comparing other species. Finally, this study confirms such ecological indicator of sustainable fisheries could be developed base on landing statistic data, however a multi-indicator should be used in order to asses the state and trend of fisheries comprehensively in certain location.